3D scaffolds coated with nanofibers displaying bactericidal activity for bone tissue applications - Sá, Kevin Domingos de (2018)
Bone-limited capacity to fully repair large defects requires the development of new implants. In this context, new approaches have been used to promote bone regeneration and also to avoid the side effects associated with the therapeutics currently used in the clinic. Herein, 3D tricalcium phosphate/alginic acid scaffolds were produced and then coated with an electrospun mesh loaded with two different antibacterial agents, silver nanoparticles, and salicylic acid. The obtained results showed that the produced scaffolds have suitable mechanical properties, swelling, biodegradation, biomineralization activity, enhanced cellular adhesion/proliferation and bactericidal activity, and features essential for bone regeneration.